The effects of melatonin administration on KCNQ and KCNH2 gene expressions and QTc interval in pinealectomised rats - Ovali, M. A.; Uzun, M. (Cellular and Molecular Biology, 2016)
Melatonin is a hormone secreted from the pineal gland and has different cardiovascular effects. KCNQ genes expressed in aorta related with vascu- lar tone and KCNH2 gene characterised in left ventricle associated with QT duration. The aim of this study was to investigate the effects of melatonin on the regulation of the blood pressure and the relationships between the expressions of aorta KCNQ1-5, left ventricle KCNH2 genes and the QTc interval. For that purpose, 42 male adult Sprague-Dawley rats were devided into six groups; SHAM, SHAM+L-NAME, PLT, PLT+L-NAME, PLT+MEL and PLT+L-NAME+MEL. Pinealectomy operation was applied in PLT groups. L-NAME was added in drinking water (40 mg/kg/day) and melatonin was given subcutanously (5 mg/kg/day). The blood pressure, heart rate (HR) and QTc interval values were recorded on 0, 1st, 7th, 14th and 21st days of experiment. Left ventricle and thoracic aorta samples were obtained to investigate the changes of gene expression levels of KCNQ1-5 and KCNH2, respectively. The increased blood pressure and HR were observed in SHAM+L-NAME, PLT, and PLT+L-NAME groups compared to MEL and SHAM groups (p<0.05). On the other hand, the long QTc interval was recorded in PLT and all L-NAME groups compared to others (p<0.05). The decreases in KCNH2 gene expression levels were observed in groups have QTc prolongation. In conclusion, PLT operation could cause an increasing in blood pressure, HR and QTc duration, melatonin was able to prevent these increasings and could change KCNQ and KCNH2 gene expresion profiles. Further molecular studies are required to evaluate these effects.